2012
DOI: 10.1289/ehp.1204962
|View full text |Cite
|
Sign up to set email alerts
|

Research Opportunities for Cancer Associated with Indoor Air Pollution from Solid-Fuel Combustion

Abstract: Background: Indoor air pollution (IAP) derived largely from the use of solid fuels for cooking and heating affects about 3 billion people worldwide, resulting in substantial adverse health outcomes, including cancer. Women and children from developing countries are the most exposed populations. A workshop was held in Arlington, Virginia, 9–11 May 2011, to better understand women’s and children’s potential health effects from IAP in developing countries. Workshop participants included international scientists, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 41 publications
0
29
0
3
Order By: Relevance
“…This type of solid fuel (biomass) is the major origin of air pollutants in such closed environments of rural properties (Balmes, 2010) .Women and children in these environments are at higher risk because of increased exposure to air pollutants (Kodgule and Salvi, 2012;Kurmi et al, 2012;Reid et al, 2012). Also, the female villagers engaged in baking home-made bread, experience consecutive hours of working by the side of traditional ovens and long-term exposure to fumes and therefore with a higher risk for air pollutant-associated diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of solid fuel (biomass) is the major origin of air pollutants in such closed environments of rural properties (Balmes, 2010) .Women and children in these environments are at higher risk because of increased exposure to air pollutants (Kodgule and Salvi, 2012;Kurmi et al, 2012;Reid et al, 2012). Also, the female villagers engaged in baking home-made bread, experience consecutive hours of working by the side of traditional ovens and long-term exposure to fumes and therefore with a higher risk for air pollutant-associated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the female villagers engaged in baking home-made bread, experience consecutive hours of working by the side of traditional ovens and long-term exposure to fumes and therefore with a higher risk for air pollutant-associated diseases. In 2010, the International Agency for Research on Cancer (IARC) declared that the pollution produced by biomass utilization is considered as a possible carcinogen for human (Reid et al, 2012). In a study reported in China in 2008, an association between the indoor air pollution (IAP) due to solid fuel and chronic respiratory disease and lung cancer was confirmed (Galeone et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Because the majority of households in developing countries rely on solid fuels for daily cooking and heating needs, there are growing concerns over air pollution from solid fuel combustion and the associated health problems [4][5][6][7]. The most recent Global Burden of Disease study (2010) estimated that the exposure to smoke from household air pollution was responsible for approximately 3.5 million premature deaths globally, as well as other various health issues, such as cataracts and cardiovascular disease [8][9][10]. The percentage of the population that relies on solid fuels as their main energy source is one of the indices in the Millennium Development Goal indicators [11].…”
Section: Introductionmentioning
confidence: 99%
“…Smoking of tobacco is undoubtly one of predominant risk factor for lung cancer (Tredaniel et al, 1994;Pisani et al, 2006;Sellappa et al, 2009). Apart from smoking exposure, indoor smoke from household activities (Zhong et al, 1999;Reid et al, 2012;Yin et al, 2013) and dietary habits (Marchand et al, 2002;Shen et al, 2008) were also suspected to have casual relationship. Exposure to cooking oil fumes (COF) and wood smoke are known to contain considerable amount of carcinogens such as benzo [a]pyrene, 2, 4-decadienal, carbon monoxide, carbon dioxide and other polycyclic aromatic hydrocarbons (PAH) (Yang et al, 2000;Lissowska et al, 2005).…”
Section: Introductionmentioning
confidence: 99%